TV시리즈 애니메이션 〈심슨가족〉에 나타난 시트콤의 특성 - 박윤오(Youn-O Park); 김재웅(Jae-Woong Kim) (한국콘텐츠학회 논문지, 11(3), 2011)
TV sitcom animation <The Simpsons> is a immensely popular to any religion and age, sex. The five yellow main characters and a great amount of sub characters appear to tell their broad stories every sequence. It makes people laugh using parody and pastiche with the American social subjects and political issues. This paper examines the study of story structures for sitcom animation and main factors of the Simpsons' popularity. The case works are focused on 'The future of korean TV sitcom animation'. TV시트콤 애니메이션 <심슨가족>은 동서양, 학력, 나이, 성별을 막론하고 다양한 수용자층을 확보하며 대중적인 인기를 누리고 있다. 5명의 주인공 가족과 다양한 주변인물들은 매회 등장하여 폭넓은 주제에 대해 이야기하며, 미국의 사회, 정치적 이슈가 되고 있는 무거운 주제들을 패러디를 사용하여 일반인들이 쉽게 받아들일 수 있도록 표현하고 있다. <심슨가족>이 전 세계에서 이와 같이 사랑받고 있는 이유를 시트콤 애니메이션이라는 새로운 형식의 스토리 전개방식과 캐릭터의 특징, 그 외의 재미요소들을 통해 분석하고, 이를 활용한 국내 시트콤 애니메이션의 전망을 살펴보고자 한다.